Polynyas and Prehistoric Settlement Patterns - Schledermann, Peter (ARCTIC, 1980)
In traditional Inuit society the availability of game resources must always have been one of the most important criteria for the determination of settlement locations. A number of ecological factors determine the availability of particular game species in the Arctic regions. The presence of open water areas known as polynyas is one of these factors. The relationship between polynya distributions and prehistoric settlement patterns in the High Arctic is explored, with particular reference to the Bache Peninsula region on the east coast of Ellesmere Island, N.W.T.